Experimental study into rotational-oscillatory vibrations of a vibration machine platform excited by the ball auto-balancer - Yatsun, Volodymyr; Filimonikhin, Gennadiy; Nevdakha, Andrey; Pirogov, Vladimir (Eastern-European Journal of Enterprise Technologies, 2018)
We have experimentally investigated the rotational-oscillatory vibrations of vibratory machine platform excited by the ball auto-balancer. The law of change in the vibration accelerations at a platform was studied using the accelerometer sensors, a board of the analog-to-digital converter with an USB interface and a PC. The amplitude of rapid and slow vibratory displacements of the platform was investigated employing a laser beam. It was established that the resonance frequency (frequency of natural oscillations) of the platform is: 62.006 rad/s for the platform with a mass of 2,000 gm; 58.644 rad/s ‒ of 2,180 gm; 55.755 rad/s ‒ of 2,360 gm. An error in determining the frequencies does not exceed 0.2 %. The ball auto-balancer excites almost perfect dual-frequency vibrations of a vibratory machine platform. Slow frequency corresponds to the rotational speed of the center of balls around the longitudinal axis of the shaft, while the fast one ‒ to the shaft rotation speed, with the unbalanced mass attached to it. A dual-frequency mode occurs in a wide range of change in the parameters and it is possible to alter its basic characteristics by changing the mass of balls and the unbalanced mass, the angular velocity of shaft rotation. It has been established experimentally that the balls get stuck at a frequency that is approximately 1 % lower than the resonance frequency of platform oscillations. Assuming the platform executes the dual frequency oscillations, we employed the software package for statistical analysis Statistica to select coefficients for the respective law. It was found that: – the process for determining the magnitudes of coefficients is steady (robust); coefficients almost do no change when altering the time interval for measuring the law of a platform motion; – the amplitude of accelerations due to the low oscillations is directly proportional to the total mass of the balls and the square of the frequency at which balls get stuck; – the amplitude of rapid oscillations is directly proportional to the unbalanced mass at the auto-balancer's casing and to the square of angular velocity of shaft rotation. The discrepancy between the law of motion, obtained experimentally, and the law, obtained using the methods of statistical analysis, is less than 3 %. The results obtained add relevance to both the analytical studies into dynamics of the examined vibratory machine and to the creation of the prototype a vibratory machine.